Influence of Socio-Economic Factors on Crime Among International Migrants in South Africa - A Sathiya Susuman; Sithole, Knowledge (African Human Mobility Review, 2024)
The presence of immigrants in South Africa has led citizens to believe that migrants are responsible for increased crime rates in the country. This belief is a harmful stereotype that has no basis in reality, as most of the crimes are not committed by the migrants. This study explores the impact of socio-economic factors on crime rates by international migrants in South Africa from 2012 to 2017. Specifically, it focuses on examining the likelihood and association between two key variables: migrants with no formal education and crime, and unemployed migrants and crime. Through chi-square tests and multinomial regression, the study investigated whether these socio-economic factors drove criminal behavior among the international migrant population. This study obtained data from secondary sources. The study’s findings revealed that unemployment has an impact on migrants and crime rates in South Africa. The relationship showed a weak association, attributed to insufficient supporting evidence due to the low statistical power of educational status. The relationship proved to not have a strong association, lacking supporting evidence due to low statistical power on educational status. The level of education among migrants did not play a substantial role in influencing criminal behavior within the South African context. Other factors, such as social networks, cultural integration, and individual characteristics, might have a more prominent influence on criminal activities among migrants. However, addressing unemployment issues among international migrants in South Africa to mitigate the risk of criminal involvement is crucial. Policymakers and stakeholders should focus on developing effective strategies to promote employment opportunities, skills development, and social integration among migrant communities. By addressing these socio-economic factors, it may be possible to reduce crime rates and create a more inclusive society for both migrants and the host population in South Africa.